Impact of income diversification on the default risk of Vietnamese commercial banks in the context of the COVID-19 pandemic - Thanh Tam Le; Quynh Anh Nguyen; Thi Minh Ngoc Vu; Minh Phuong Do; Manh Dung Tran (Cogent Business & Management, 2022)
This study is aimed to examine the impact of income diversification on bank risk in Vietnam before and during the COVID-19 pandemic by studying commercial banks over the period 2012-2020. By employing the fixed effects model (FEM) and general least squares model (FGLS), our main result shows that the higher the level of income diversification, the lower the risk of default. However, the diversification strategy should be conducted based on each source of non-interest income, in particular banks need to limit the increase in direct income from service activities, and reduce service fees to increase other indirect revenues, such as benefiting from transaction size and CASA value. This is different from previous studies. Besides, banks should improve the quality of foreign exchange business, securities investment and increase income from other non-interest activities. We also find that bank's default risk tends to decrease when the COVID-19 pandemic breaks out. However, contrary to our hypothesis, the impact of the COVID-19 pandemic on the relationship between income diversification and default risk of commercial banks in Vietnam has not been confirmed.
Keywords: 650; bank risk; COVID-19 pandemic; default risk; diversification; interest income; non-interest income